Fray Martín de Rada, evangelizador, cosmógrafo y embajador en China - Ostolaza Elizondo, Isabel (Huarte de San Juan. Geografía e Historia, 2006)
The article gathers the evolution of this navarresse celebrity forgotten by the Historiography, one of the great missionaries and cosmographers who took part in the plans of the Spanish Crown in their expansion by the Orient. In his short vital development, he died at the age of 45; he specially did a huge work in his last stage in The Philippines, being the first ambassador of the Catholic Monarchy in Chine. His open mind and his vast scientific curiosity took to him to profit from his short stay in the Empire, getting a lot of books about the country which were useful as inspiration source for the elaboration of the history of China by the Europeans. History that gathers certain stereotypes that in the European imaginary will become the idealized vision that a short stay visitor could have on the country, as the recent works of Manel Ollé stand out. It is the image of the millenarian China without going deeply on its internal mysteries but, in any case it is a more updated vision that the one of Marco Polo, on which Europe had lived during centuries.